2019
DOI: 10.1016/j.cegh.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Determinant factors of drug resistant tuberculosis in Iran, a case control study

Abstract: Introduction: Drug resistance is one of the critical aspects had to be considered in the tuberculosis control program. Factors related to drug resistance are different in geographic regions and vary during the time. The present study aims to determine the risk factors of drug resistance among TB patients in northern of Iran. Methods: In this case control study, 22 cases (drug resistant TB patients) and 88 controls (TB patients selected out of those with successive treatment) were randomly selected from a cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
3
4
1
Order By: Relevance
“…This was in line with the study that was conducted in East Shoa (11). However, MDR-TB was not associated with residence according to the studies that were conducted in Jimma (13), China (26) and Iran (27). This difference might be due to access of TB services nearby and low knowledge of TB for drug adherence, transportation problem, inadequate social support and fear of stigma to complete anti-TB drugs.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This was in line with the study that was conducted in East Shoa (11). However, MDR-TB was not associated with residence according to the studies that were conducted in Jimma (13), China (26) and Iran (27). This difference might be due to access of TB services nearby and low knowledge of TB for drug adherence, transportation problem, inadequate social support and fear of stigma to complete anti-TB drugs.…”
Section: Discussionsupporting
confidence: 83%
“…And previous treatment was a major predictor of MDR-TB in this study. Similar ndings were found in a number of studies from different countries including the Ethiopia, East Shoa(11), Amhara regional state(32), Addis Ababa(10), Iran and neighboring countries (38),Iran (27),Nepal (39),China(26),Sub-Saharan countries review(9), retrospective study in Nigeria(40), Equatorial Guinea(34), Tanzania(33), USA(4). Systematic review and meta-analysis in Ethiopia(12) revealed previous treatment was a major determinant of MDR-TB, systematic review in Europe (41).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Resistance to rifampicin and isoniazid is a resistance that often occurs when undergoing tuberculosis treatment, this resistance allows for a wider and more difficult resistance called XDR-TB (Extensively drug resisten tuberculosis). 50 Previous tuberculosis treatment was the most significant predisposing factor causing resistance, this was stated by Mesfin et al in a study conducted in Ethiopia, 27 the same thing was stated by Arora et al in an article discussing drug resistance tuberculosis tuberculosis; 49 similar findings in a study in western France, 37 northern part of Iran, 21 Henan Province China, 5 Malaysia 32 and research in Espírito Santo, Brazil. 40 The results of this study are somewhat different from the research conducted in Serbia by Stosic et al which stated that a significant predisposing factor for drug resistance was an economic factor.…”
Section: Multi-drug Resistance Tuberculosis (Mdr-tb) Is Drug-resistan...mentioning
confidence: 74%
“…Very important to identify matters related to the success of treatment in order to avoid resistance. 21 Risk factors for resistance include those who relapse after receiving successful treatment, those who return after failure, and those who start receiving a treatment regimen after experiencing previous treatment failure. 5 Some of the things that cause failure are drugs used to treat TB are not used as prescribed.…”
Section: Multi-drug Resistance Tuberculosis (Mdr-tb) Is Drug-resistan...mentioning
confidence: 99%